Environmental Problems in Preschool Children - Dilnoza Alijanovna Karimjonova (Euro Asian Journal Publishing, 2023)
The main goal of environmental education is to develop in preschool children a conscious attitude to the environment and its problems, as well asthe knowledge, skills and competencies to find optimal solutions to them. In this sense, the article analyzes the purpose of environmental education in preschool education.
Keywords: ecology; preschool children; ecological upbringing